2010
DOI: 10.1111/j.1600-0706.2009.17848.x
|View full text |Cite
|
Sign up to set email alerts
|

Does urbanization select for weak competitors in house sparrows?

Abstract: How urbanization affects animal populations is in the focus of current ecological research. Existing theory of this topic suggests that the cities' more constant food supplies and lower predation pressure lead to a high proportion of weak competitors in urban populations. To evaluate this hypothesis, we tested whether competitive performance differs between differently urbanized populations of house sparrows Passer domesticus. We previously showed that wild urban sparrows are smaller and leaner than rural cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
6
29
1
1
Order By: Relevance
“…In line with this finding, elevated levels of male territorial aggression have been found in urban song sparrows Melospiza melodia, compared to rural male conspecifics. However, this pattern is not necessarily supported in other species (Newman et al, 2006;Bókony et al, 2010;Atwell et al, 2014;Hasegawa et al, 2014). Furthermore, bird species living in urban landscapes have been shown to peck in lower frequencies in response to handling than those inhabiting rural habitats (Møller and Ibáñez-Álamo, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…In line with this finding, elevated levels of male territorial aggression have been found in urban song sparrows Melospiza melodia, compared to rural male conspecifics. However, this pattern is not necessarily supported in other species (Newman et al, 2006;Bókony et al, 2010;Atwell et al, 2014;Hasegawa et al, 2014). Furthermore, bird species living in urban landscapes have been shown to peck in lower frequencies in response to handling than those inhabiting rural habitats (Møller and Ibáñez-Álamo, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Likewise, studies of the house sparrow found no evidence of any systematic, urbanization-related differences in stress responses, physiology, coloration, or body condition of adults, although birds of urbanized habitats were found to be proportionally smaller (but not leaner) compared to their rural conspecifics (Liker et al 2008. In another study, urban and rural sparrows neither differed in their competitive performance, nor did the authors found any relation between individuals' body mass, competitive success or in variance of competitive abilities (BÓkony et al 2010). Similarly, a recent study on the song sparrow failed to find detrimental effects of increased habitat urbanization on birds' stress physiology and body condition (Grunst et al 2014).…”
Section: Changes In Resource-based Forcesmentioning
confidence: 85%
“…Also, the competition for resources in large populations has not been confirmed to be the reason behind the weaker condition of the urban House sparrows, which has been proven in an experiment conducted in a mixed flock of sparrows from urban and rural areas. These birds, kept in captivity under the same conditions and under the influence of various factors, showed no differences in their ability to compete (Bókony et al 2010).…”
Section: Introductionmentioning
confidence: 91%